Sosialisasi Pemanfaatan Tumbuhan Obat sebagai Hasil Hutan Bukan Kayu (HHBK) di Desa Domato Kecamatan Jailolo Selatan Kabupaten Halmahera Barat - Nurhikmah; Siti Nurjannah; Adesna Fatrawana; Sabaruddin; Laswi Irmayanti (Altifani Journal: International Journal of Community Engagement, 2024)
Non-Timber Forest Products (NTFPs) are biological forest products, both vegetable and animal and their derivatives originating from forests except wood. NTFPs have an important role for the community because they can increase household income, can improve the local economy, while still preserving forests. One of the NTFPs that people often use is medicinal plants. Community service activities are carried out by providing outreach to the community regarding the use of medicinal plants that can be used in daily life according to disease indications. The series of community service activities carried out are the delivery of Forestry Study Program activities, the delivery of material related to the use of medicinal plants, and the delivery of forestry books which can increase public information regarding the use of forests and forest products.